Amine-free melanin-concentrating hormone receptor 1 antagonists: Novel 1-(1H-benzimidazol-6-yl)pyridin-2(1H)-one derivatives and design to avoid CYP3A4 time-dependent inhibition. Issue 11 (1st June 2016) - Igawa, Hideyuki; Takahashi, Masashi; Shirasaki, Mikio; Kakegawa, Keiko; Kina, Asato; Ikoma, Minoru; Aida, Jumpei; Yasuma, Tsuneo; Okuda, Shoki; Kawata, Yayoi; Noguchi, Toshihiro; Yamamoto, Syunsuke; et al.
Graphical abstract: Abstract: Melanin-concentrating hormone (MCH) is an attractive target for antiobesity agents, and numerous drug discovery programs are dedicated to finding small-molecule MCH receptor 1 (MCHR1) antagonists. We recently reported novel pyridine-2(1 H )-ones as aliphatic amine-free MCHR1 antagonists that structurally featured an imidazo[1, 2- a ]pyridine-based bicyclic motif. To investigate imidazopyridine variants with lower basicity and less potential to inhibit cytochrome P450 3A4 (CYP3A4), we designed pyridine-2(1 H )-ones bearing various less basic bicyclic motifs. Among these, a lead compound6a bearing a 1 H -benzimidazole motif showed comparable binding affinity to MCHR1 to the corresponding imidazopyridine derivative1 . Optimization of6a afforded a series of potent thiophene derivatives (6q –u ); however, most of these were found to cause time-dependent inhibition (TDI) of CYP3A4. As bioactivation of thiophenes to form sulfoxide or epoxide species was considered to be a major cause of CYP3A4 TDI, we introduced electron withdrawing groups on the thiophene and found that a CF3 group on the ring or a Cl adjacent to the sulfur atom helped prevent CYP3A4 TDI. Consequently, 4-[(5-chlorothiophen-2-yl)methoxy]-1-(2-cyclopropyl-1-methyl-1 H -benzimidazol-6-yl)pyridin-2(1 H )-one (6s ) was identified as a potent MCHR1 antagonist without the risk of CYP3A4 TDI, which exhibited a promising safety profile including low CYP3A4 inhibition and exerted significant antiobesity effects in diet-induced obese F344 rats.